Tra rivoluzione e controrivoluzione. L’interpretazione gramsciana del fascismo - Alessio Gagliardi (Laboratoire Italien)
The article examines the main categories and lines of analysis developed by Gramsci in his analysis of fascism. In order to fully understand fascism’s particular characteristics, he developed a reading that brought into play a more general interpretation of the history of Italy and the processes of transformation typical of the capitalist societies of his time. This consisted in an analytical apparatus that evolved over time, with the change in Gramsci’s conditions of existence and degree of political involvement, and with the different successive phases of the fascist movement and the dictatorship. The article examines his whole political and intellectual itinerary, with special reference to the reflection carried out during his detention and written down in the Prison Notebooks. The categories that Gramsci developed in this phase are grouped around three clusters of problems which in some cases take up again suggestions and traces of analyses sketched out previously: social classes and historical periods, forms of command (a subject connected with the reflection on “caesarism”-“bonapartism” and on the intellectuals), and “passive revolution” and the nexuses with the changes in capitalism and Fordist modernization.